2008
DOI: 10.1016/j.ygeno.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of necrosis and apoptosis induced by 5-fluoro-2′-deoxyuridine

Abstract: 5-Fluoro-2'-deoxyuridine (FUdR), a potent anticancer agent, exerts its effects by inhibiting thymidylate synthase, an essential machinery for DNA synthesis in cell proliferation. Also, cell death is caused by FUdR, primarily due to an imbalance in the nucleotide pool resulting from this enzyme inhibition. We have investigated the cancer cell death induced by FUdR, focusing on its molecular mechanisms. Using mouse mammary tumor FM3A cell lines, the original clone F28-7 and its variant F28-7-A cells, we previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…6 Reports from other laboratories have shown that mitochondria play a role in mediating both necrosis and apoptosis. [25][26][27] Interestingly, a number of the mitochondrial proteins exhibit differential expressions in F28-7 and F28-7-A cells either in the untreated stages or in the FUdR-treated stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Reports from other laboratories have shown that mitochondria play a role in mediating both necrosis and apoptosis. [25][26][27] Interestingly, a number of the mitochondrial proteins exhibit differential expressions in F28-7 and F28-7-A cells either in the untreated stages or in the FUdR-treated stages.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 FUdR, a potent anticancer agent, exerts its effect by inhibiting thymidylate synthase, an essential machinery for DNA synthesis in cell proliferation (see ref 7 and references therein). Previously, we reported that the treatment can induce in F28-7 cells a breakdown of DNA into chromosome-sized fragments leading to necrosis, and that it can induce in F28-7-A more extensive DNA cleavage into oligonucleosome-sized fragments and subsequent development of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sato et al [49] determined the gene expression profile induced by an anticancer agent, 5-fluoro-2 0 -deoxyuridine (FUdR), in mouse mammary FM3A tumors to elucidate the molecular mechanisms regulating necrosis. In another example, TNFa activated RIP 1 kinase-mediated signaling for the induction of downstream genes influencing necrosis or apoptosis, as revealed by Hitom et al [50].…”
Section: Vp3 Localizationmentioning
confidence: 99%
“…Recently, investigating the molecular mechanisms regulating necrosis, Sato et al [43] identified the gene expression profile induced by an anticancer agent, 5-fluoro-2 0 -deoxyuridine (FUdR), in mouse mammary FM3A tumors, which required gene expression for triggering their necrosis [43]. On the other hand, TNF a activates the RIP 1 kinase-mediated signaling for the induction of downstream genes influencing necrosis or apoptosis [44,45].…”
Section: Discussionmentioning
confidence: 99%